2017
DOI: 10.21831/jipi.v3i1.13678
|View full text |Cite
|
Sign up to set email alerts
|

Developing PBL kit by utilizing blog in order to improve scientific process and problem solving skills in physics learning

Abstract: The study aimed at generating PBL-based learning kit product by utilizing blog, at meeting the criteria of learning kit feasibility, at testing the effectiveness of learning kit that the researcher had developed and at identifying the learning participants’ scientific process and problem solving skills. In conducting the study, the researcher implemented the 4-D Model. The learning kit development started involved preliminary study, product design, expert and practitioner test, limited experiment and field exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 4 publications
1
1
0
2
Order By: Relevance
“…The analysis did not reveal a significant effect between instructor quality and perceived usefulness (H2). This outcome aligns with the findings of previous studies that also did not find a significant impact of instructor quality on perceived usefulness (Haji et al, 2015;Moore & Perkins, 2018;Ulva, 2017), but contradicts with the findings of the study by (Bakar et al, 2023;Lathifah et al, 2023). This shows that the quality of the instructor does not influence the perceived usefulness of using Phet simulation based on Problem Based Learning.…”
Section: Hypothesis Testingsupporting
confidence: 66%
See 1 more Smart Citation
“…The analysis did not reveal a significant effect between instructor quality and perceived usefulness (H2). This outcome aligns with the findings of previous studies that also did not find a significant impact of instructor quality on perceived usefulness (Haji et al, 2015;Moore & Perkins, 2018;Ulva, 2017), but contradicts with the findings of the study by (Bakar et al, 2023;Lathifah et al, 2023). This shows that the quality of the instructor does not influence the perceived usefulness of using Phet simulation based on Problem Based Learning.…”
Section: Hypothesis Testingsupporting
confidence: 66%
“…Phet also provides various experiments if inadequate laboratory tools and materials are available (Astuti & Handayani, 2018). The study's results revealed that problem-based learning (PBL) with information and communication technology greatly increased students' basic competence in science learning (Ulva, 2017). As we know that the PBL learning model provides a problemsolving process that is guided by the teacher to assist students in understanding subject concepts through problem-solving solutions (Haji et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Dalam pengembangan media pembelajaran, pendidik harus memperhatikan model yang diterapkan. Apakah model tersebut dapat menciptakan hasil pembelajaran secara efektif dan kompeten (Ulva, 2017). Serta media pembelajaran harus menarik dan mudah digunakan yang diharapkan mampu merangsang untuk meningkatkan pemahaman dan keterampilan siswanya.…”
Section: Pendahuluanunclassified
“…Jika dilihat dari segi digital leraning, tenaga pendidik dapat beradaptasi dalam menggunakan system, dimana masa pandemi memaksa semua sektor untuk bertransformasi menggunakan teknologi. Hal yang perlu diperhatikan tenaga pendidik adalah memastikan apakah model pembelajaran yang digunakan dapat menciptakan hasil pembelajaran secara efektif dan kompeten (Ulva, 2017). Banyaknya manfaat dari penggunaan model blended learning juga sebanding dengan hasil belajar mahasiswa dalam memahami setiap materi yang diberikan.…”
Section: Perangkat Pembelajaran Untuk Menunjang Rpp Tersebut Yaitu Media Lengkap Untuk Matakuliahunclassified